Hubungan Religiutas dengan Kebahagiaan pada Remaja di Panti Asuhan Betlehem Bandar Baru - Evi Malinda Tarigan; Azhar Azis (Jouska: Jurnal Ilmiah Psikologi, 2022)
This study aims to determine and empirically test the relationship between religiosity and adolescent happiness at the Bethlehem Orphanage in Bandar Baru. The type of research used in this study is a quantitative approach. The population is 82 teenagers at the Bethlehem Orphanage in Bandar Baru. The number of samples in this study were 82 people. The sampling technique used is the total sampling technique. Both scales use a Likert scale. The religiosity scale is based on aspects that affect religiosity according to Glock Strack (in Marza, 2006), namely: Religious practice, Religious belief, Religious knowledge, Religious feeling, Religious effect. The happiness scale is based on aspects according to Seligman et al. (2005), namely: Establishing positive relationships with others, Full involvement, Finding meaning in everyday life, Optimistic, but still realistic, Being a resilient person. Based on the results of the analysis using the r Product Moment correlation analysis method, it is known that there is a positive relationship between religiosity and happiness, where rxy = 0.522 with a significant p = 0.000 0.050. This means that the proposed hypothesis is accepted. The determinant coefficient (r2) of the relationship between the independent variable X and the dependent variable Y is r2 = 0.272. This shows that religiosity contributes to happiness by 27.2%. Based on the results of the calculation of the hypothetical and empirical average values, it can be concluded that religiosity is high with a hypothetical mean value of 90 and an empirical mean of 99.69. Furthermore, it can also be concluded that happiness is classified as high with a hypothetical value of 100 and an empirical value of 113, 88.